Effects of Reducing the Digestible Lysine and Tryptophan to Lysine Ratio on Growth Performance of Grow-Finish Pigs - Andres F. Tolosa; Mike D. Tokach; Robert D. Goodband; Jason C. Woodworth; Joel M DeRouchey; Jordan T. Gebhardt; Craig Steck; Matt L. Wolfe (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 1,080 finishing pigs (327 × 1050, PIC; initially 71.3 ± 1.91 lb) were used in a 119-d growth trial to evaluate the effects of reducing the dietary SID Lys and SID Trp:Lys ratio on growth performance to find strategies to reduce growth rate of pigs during the grow-finish period. Pigs were allotted by initial BW and randomly assigned to 1 of 4 dietary treatments in a completely randomized block design with 27 pigs per pen and 10 pens per treatment. Dietary treatments were corn-soybean meal-based diets with DDGS. Three dietary regimes were formulated to contain either 100, 90, or 80% of the estimated SID Lys requirement for pigs in this facility, and these diets had a SID Trp:Lys ratio of 19%, with the exception of the last dietary phase formulated to 17% SID Trp:Lys. A fourth regime was formulated to 80% SID Lys with a SID Trp:Lys ratio of 16% (80–16% SID Trp:Lys) throughout all phases. Overall, from d 0 to 119, ADG and final BW decreased (linear,P<0.001) and F/G tended to worsen (linear,P= 0.087) as SID Lys decreased from 100 to 80% of the requirement. Pigs fed the diet with 80–16% SID Trp:Lys also had decreased ADG and poorer F/G compared with pigs fed 80% of the SID Lys requirement with high a Trp:Lys ratio. In conclusion, reducing SID Lys decreased growth performance and final BW of pigs during the grow-finish period. A further reduction in Trp:Lys ratio also decreased ADG and tended to worsen feed efficiency. This resulted in a 25 lb difference in final BW between pigs fed Lys and Trp at the requirement (100%) compared with pigs fed the 80% SID Lys and 16% Trp:Lys ratio. This study provides alternatives to producers to reduce growth rate of finishing pigs.
Keywords: lysine; tryptophan; slow down growth; grow-finish pig